(untitled) (Raparin Journal of Humanities (RJH), 2025)
The present study is an investigation into the multimodal discourse analysis of campaign posters used by political parties, political coalitions, and independent candidates during the 2024 parliamentary elections in the Iraqi Kurdistan Region. In the current study, the researchers will utilize a multimodal discourse analysis approach so as to explore and find out how meanings are constructed and communicated through different modes such as verbal, visual, audio and so on. The main objective is to examine the various tools and strategies employed by the political candidates in designing the posters to convey their plans, programs, and appeal to the electorate. To conduct a comprehensive exploration of the multimodal discourse in the 2024 parliamentary election campaigns of the Iraqi Kurdistan Region, the present study will analyze a sample of five campaign posters of four nominees from four different political parties and one independent candidate. The posters have been carefully selected to represent a diverse range of political parties and independent candidates. The findings demonstrate how nominees use linguistic components, including Kurdish text and straightforward, uncomplicated language, to demonstrate their sense of politics and their self-confidence. Additionally, the employment of social markers and close facial expressions increases connection and audience participation.